Glycodeoxycholic acid as alternative treatment in 3β-hydroxy-Δ5-C27-steroid-oxidoreductase: a case report - Majait, S.; Vaz, F. M.; Kemper, E. Marleen; Bootsma, A. H.; Groen, A. K.; Nieuwdorp, M.; Soeters, Maarten R. (Frontiers in Pediatrics, 2024)
Background: 3β-hydroxy-Δ5-C27-steroid-oxidoreductase (3β-HSD) deficiency is a bile acid synthesis disorder that leads to the absence of normal primary bile acids and the accumulation of abnormal bile acids. This results in cholestatic jaundice, fat-soluble vitamin deficiency, acholic or fatty stools and failure to thrive. Bile acid supplementation is used to treat 3β-HSD-deficiency and its symptoms.Methods: This report details the case of a 28-year-old woman diagnosed with 3β-HSD-deficiency, who was treated with glycine-conjugated deoxycholic acid (gDCA).Results: gDCA treatment successfully restored normal bile acid levels, improved body weight by reducing fat malabsorption, and was well-tolerated with no observed liver problems or side effects.As a potent FXR ligand, gDCA might exert its action through FXR activation leading to bile acid synthesis regulation.